2004
DOI: 10.1124/jpet.103.064808
|View full text |Cite
|
Sign up to set email alerts
|

Activation of μ-Opioid Receptors Inhibits Synaptic Inputs to Spinally Projecting Rostral Ventromedial Medulla Neurons

Abstract: The rostral ventromedial medulla (RVM) is a major locus for the descending control of nociception and opioid analgesia. However, it is not clear how opioids affect synaptic inputs to RVM neurons. In this study, we determined the effect of -opioid receptor activation on excitatory and inhibitory synaptic transmission in spinally projecting RVM neurons. RVM neurons were retrogradely labeled with a fluorescent tracer injected into the dorsal horn of the spinal cord in rats. Whole-cell voltage-clamp recordings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 39 publications
3
38
1
Order By: Relevance
“…Electrophysiological studies indicate that MOR agonists inhibit synaptic transmission in the RVM by both postsynaptic and presynaptic mechanisms (Pan et al, 1990;Marinelli et al, 2002;Finnegan et al, 2004). In contrast, DOR-like immunoreactivity is predominantly located on presynaptic elements in the RVM (Kalyuzhny et al, 1996;Ma et al, 2006), although the presence of postsynaptic DOR is suggested by the ability of DELT to hyperpolarize a subpopulation of RVM neurons (Marinelli et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Electrophysiological studies indicate that MOR agonists inhibit synaptic transmission in the RVM by both postsynaptic and presynaptic mechanisms (Pan et al, 1990;Marinelli et al, 2002;Finnegan et al, 2004). In contrast, DOR-like immunoreactivity is predominantly located on presynaptic elements in the RVM (Kalyuzhny et al, 1996;Ma et al, 2006), although the presence of postsynaptic DOR is suggested by the ability of DELT to hyperpolarize a subpopulation of RVM neurons (Marinelli et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…The G-protein inhibitor, GDP-␤-S (1 mM), was added to the internal solution in the evoked protocol to eliminate the potential postsynaptic effect of opioids (Pan et al, 2002. Also, the internal pipette solution contained 0.2% biocytin (Sigma-Aldrich, St. Louis, MO) to label the recorded neuron for later use in the immunofluorescence labeling (Finnegan et al, 2004). The brain slice was placed in a glass-bottomed chamber (Warner Instrument, Hamden, CT) and fixed with a grid or parallel nylon threads supported by a U-shaped stainless steel weight.…”
Section: Methodsmentioning
confidence: 99%
“…Miniature inhibitory postsynaptic currents (mIPSCs) and miniature excitatory postsynaptic currents (mEPSCs) were recorded at a holding potential of 0 and Ϫ70 mV, respectively (Pan et al, 2002;Finnegan et al, 2004). All mIPSCs were recorded in the presence of tetrodotoxin (TTX; 1 M) and 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX; 20 M).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, activation of presynaptic μ-opioid receptors primarily attenuates GABAergic synaptic input in the amygdala (Finnegan et al, 2005;Finnegan et al, 2006). Opioids also reduce synaptic GABA release to spinally projecting neurons in the rostral ventromedial medulla (Finnegan et al, 2004) and periaqueductal gray (Vaughan et al, 1997). Furthermore, through presynaptic inhibition of GABA release, activation of δ-opioid receptors may disinhibit spinally projecting noradrenergic neurons in the locus coeruleus (Pan et al, 2002a).…”
Section: Effect Of Opioid Receptor Agonists On Synaptic Transmissionmentioning
confidence: 99%